SCASP: A Simple and Robust SDS-Aided Sample Preparation Method for Proteomic Research - Gan, Guohong (Mol Cell Proteomics, 2021)
SDS is widely used in sample preparation for proteomic research. However, SDS is incompatible with LC and electrospray ionization. SDS depletion is therefore required ahead of LC–MS analysis. Most of current SDS removal strategies are time consuming, laborious, and have low reproducibility. Here, we describe a method, SDS–cyclodextrin (CD)-assisted sample preparation, by which CD can bind to SDS and form CD–SDS complexes in solutions, allowing for direct tryptic digestion. We demonstrate that SDS–CD-assisted sample preparation is a simple, fast, and robust SDS-based sample preparation method for proteomics application.